Covid-19: Reinforcing Gender Gaps? - Clara Albrecht; Victoria Endl-Geyer; Tanja Stitteneder (CESifo Forum, 2021)
The pandemic has had a major impact on our society and reinforces gender gaps in many areas. Looking at unemployment figures, these have been affected, but not always to the high degree one would have expected. One reason for this may have been appropriate policy measures in some countries, especially within the EU. However, women tend to work in sectors that are badly hit by the crisis, putting them at risk of job and income losses. While gender differences are rarely clearly visible in general, they become more apparent among parents. A holistic view, however, shows that the total workload of paid and unpaid work has increased significantly more for women than for men across countries. This is reflected in the fact that women are increasingly taking on care and housework tasks, making greater use of remote work options and shifting their paid working hours into the evening. The extent to which working from home and changes in availability influence career opportunities still needs to be clarified. However, other consequences can already be observed, such as higher susceptibility to psychological problems among women. Also, preliminary data show that women face more prolonged health consequences, due to missed checkups for example, and are more likely to be victims of domestic violence during a lockdown.
Keywords: 330